Work environment factors contributing to burnout for university teachers in Kazakhstan - Nabidullin, A.S.; Zadakhanova, A.A.; Ismailova, D.B. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The study explores work environment factors contributing to burnout among university teachers in Kazakhstan. Using a descriptive survey design, data were collected from 113 faculty members across pedagogical universities to examine perceptions of workload, time management, work-balance, and institutional support. The results reveal that excessive workload and administrative responsibilities are major contributors to emotional exhaustion and disengagement from teaching duties. More than half of the respondents reported feeling overwhelmed, while a smaller proportion demonstrated resilience and effective coping strategies. Positive aspects emerged through collegial relationships and recognition, which were found to mitigate burnout and enhance motivation. However, perceptions of administrative responsiveness to faculty concerns regarding stress and well-being were divided, reflecting inconsistencies in institutional practices. The study concludes that burnout is a systemic issue influenced by organizational structures, support mechanisms, and recognition systems rather than solely individual factors. These findings underscore the significance of promoting balanced workloads, strengthening administrative engagement, and fostering a supportive academic culture to sustain teacher wellbeing and productivity within Kazakhstan’s higher education institutions.